(untitled) (Research, Society and Development, 2022)
Introduction: Palliative Care (PC) is presented as an important tool in the assistance of the health service, gaining space in Brazil in recent decades. The physical therapist’s academic training addresses general content about the death/dying binomial and palliative care. However, it is known that the physical therapist working in the intensive environment needs to understand the process of terminality. Objectives: to analyze the knowledge of the physical therapist working in the Intensive Care Unit about palliative care, identify factors that converge and diverge in the knowledge of professionals about the proposed theme and list the possibilities of action of the physical therapist with these patients within the intensive environment. Methodology: Exploratory research, of mixed character, carried out in the Intensive Care Unit of a hospital in the city of São Paulo, the sample consisted of 12 physical therapists and the data collected were analyzed by descriptive statistics and the proposed Content Analysis technique by Bardin. Results: The quantitative results indicate that professionals have satisfactory knowledge about the main concepts that guide the practice of PC. Four thematic axes were extracted, namely: promotion of patient comfort, management of mechanical ventilation/palliative extubation, maintenance of patient functionality and multidisciplinary action in PC. It was supposed the existence of ethical dilemmas and weaknesses regarding institutional processes in PC. Conclusion: It is important that there is a change in paradigms about PC and terminality in order to individualize patient care and that continuing education actions are carried out in the hospital context.